Row the boat : a never-give-up approach to lead with enthusiasm and optimism and improve your team and culture - Gordon, Jon, 1971-; Fleck, P. J., 1980- (John Wiley & Sons, Inc., 2021)
"I had followed PJ Fleck's coaching career for years since he built the Western Michigan University (WMU) football team into a national powerhouse. I always admired his positive energy and passion and could tell he was a great culture builder and leader. I also had heard stories about him from Brad Black whose company HumanEx performed the talent search and evaluation of head coaching candidates for WMU. Brad recommended to the leaders of WMU that they hire PJ Fleck despite his lack of qualifications, lack of head coaching experience and unimpressive resume. Brad's assessment tools, used to evaluate people and predictive leadership performance, told him that PJ would shine as a head coach and build a winning culture and team and that's exactly what happened. After proving himself as a successful head coach at Western Michigan taking a program from 1-11 to 13-1 during his four years, PJ Fleck was hired as the head coach of the University of Minnesota football team during a tumultuous time. Once again PJ turned around a program in need of a cultural change (academically, athletically, socially) and built a winning culture on and off the field and team that won 11 games for the first time since 1904, accomplished numerous academic records and made a program more about serving and giving than just winning games. After the season I invited PJ to be on my podcast and one of the questions I asked him was how he got into coaching. After the podcast I asked him to tell me more about his journey. The story he told me was more than a story about how he got into coaching. It was about the man himself and what led him to become the kind of coach he is."--